2016
DOI: 10.1007/s11136-016-1433-0
|View full text |Cite
|
Sign up to set email alerts
|

Proxy-reported quality of life in adolescents and adults with dyskinetic cerebral palsy is associated with executive functions and cortical thickness

Abstract: Cognitive flexibility predicts proxy report CP QOL-Teen total score in dyskinetic CP. This relationship has its anatomical correlate in the posterior cingulate and precuneus cortices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 59 publications
1
25
1
1
Order By: Relevance
“…The laterality observed in cognitive flexibility is not consistent with a previous study in unilateral CP assessing the four executive function domains (Bodimeade et al, 2013) but it was consistent with a previous study of cortical thickness in dyskinetic CP including 28 of the participants included in the present study (Laporta-Hoyos et al, 2017). This interhemispheric difference observed with the WCST has also been previously described in other neurological conditions (Jodzio et al, 2016).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The laterality observed in cognitive flexibility is not consistent with a previous study in unilateral CP assessing the four executive function domains (Bodimeade et al, 2013) but it was consistent with a previous study of cortical thickness in dyskinetic CP including 28 of the participants included in the present study (Laporta-Hoyos et al, 2017). This interhemispheric difference observed with the WCST has also been previously described in other neurological conditions (Jodzio et al, 2016).…”
Section: Discussionsupporting
confidence: 61%
“…Lesions of the basal ganglia and thalamic systems may impair focused attention and executive function (Bottcher, 2010). These brain lesions are frequently described in people with dyskinetic CP (Bax et al, 2006, Himmelmann and Uvebrant, 2011) but only one study has focused on executive function (executive function) and brain magnetic resonance imaging (MRI) in this CP subtype (Laporta-Hoyos et al, 2017). Although executive functions depend on the integrity of the entire brain, they are mainly mediated by the frontal lobes and its connections with posterior and subcortical brain regions (Anderson, 2008, Bodimeade et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…children who are not able to use speech as mode of communication) struggle with literacy despite normal cognition . Recently, executive functioning has been the focus in studies of the dyskinetic subtype, but it has not been confirmed that they struggle more in this area than those in the subgroup with spasticity …”
Section: Resultsmentioning
confidence: 99%
“…In this second largest subtype, constituting 6% to 15% of the total population with CP, 4,12 wide variability in standardized scores on tests of non-verbal reasoning and verbal comprehension (55-119) is reported. 60,61 Often 50% to 60% are reported to have an IQ less than 70, 4,5,9 but it varies between as few as 25% 11,62 and as many as 70% to 80%. 8,63 As in spastic CP, normal cognition is also found in those with the most severe motor impairments.…”
Section: Dyskinesiamentioning
confidence: 99%
“…Executive functioning is also essential for social problem solving and emotional regulation in children and young people with CP [3,9]. EF has been shown to play an important role in the QOL of people with CP [10].…”
Section: Introductionmentioning
confidence: 99%